The effect of organic powdered cottonii concentration and types of plasticizers on the characteristics of edible film. Issue 1 (March 2020) - Fransiska, D; Giyatmi,; Basmal, J; Susanti, E
Abstract: Edible film is a thin layer that can be used as an alternative packaging or food coating that can be eaten along with the products labelled with. One of the materials used to make an edible film is Organic Powdered Cottonii (OPC), a product containing carrageenan and produced from Eucheuma cottonii seaweed. This research used Completely Random Factorial Design (RALF) method with two factors, namely PC concentration (A) with four levels (1 %; 1.5 %; 2 %; 2.5 %) and types of plasticizer (B) with three levels (Glycerol; PEG; Sorbitol) with three replications. The results showed that PC concentration had a significant effect (sign <α (0.05)) on the parameters of moisture content, thickness, tensile strength, elongation, and water solubility. Different types of plasticizers have significant effects (sign< α (0.05)) on the moisture content, thickness, tensile strength, elongation, water solubility, and water vapor transmission rate (WVTR). There is an interaction between PC concentration and a type of plasticizer in PC concentration of 2.5 % and the type is sorbitol. The results of the edible film yield moisture content value of 8.30 %, thickness value of 0.09 mm, tensile strength of 12.08 MPa, elongation value of 1.67 %, water solubility value of 49.99 %, and water vapor transmission rate of 3.30 g/cm 2 /24 hours.